2017
DOI: 10.1037/tep0000141
|View full text |Cite
|
Sign up to set email alerts
|

Women in health service psychology programs: Stress, self-care, and quality of life.

Abstract: Due in part to gender roles and their socialization as caretakers, women in health service psychology (HSP) programs may be vulnerable to experiencing stressful events that negatively impact their professional and academic functioning. Two constructs are particularly germane to understanding the stress experienced by women in HSP programs: quality of life and self-care. However, scant literature exists on women in HSP programs, especially concerning the relations among stress, self-care, and quality of life. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
3
14
0
1
Order By: Relevance
“…Therefore, our results suggest that adopting self-care activities can improve people’s well-being during the COVID-19 lockdown, but the higher the perceived stress of the situation, the more difficult it is to engage in self-care activities, resulting in a lower perception of psychological well-being. The present results are in line with those studies conducted in psychology students 16 or professionals 13 which have shown a relationship between personal care and well-being. In the same way, in the context of COVID-19 pandemic, improvement in personal resources seems to be relevant to overcome stress and its associated health problems.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, our results suggest that adopting self-care activities can improve people’s well-being during the COVID-19 lockdown, but the higher the perceived stress of the situation, the more difficult it is to engage in self-care activities, resulting in a lower perception of psychological well-being. The present results are in line with those studies conducted in psychology students 16 or professionals 13 which have shown a relationship between personal care and well-being. In the same way, in the context of COVID-19 pandemic, improvement in personal resources seems to be relevant to overcome stress and its associated health problems.…”
Section: Discussionsupporting
confidence: 93%
“…[7][8][9][10][11] In contrast, the adoption of self-care activities and health behaviours could play a critical role in the prevention of immediate and subsequent complications. 12 However, its role has been especially studied in patients with chronic conditions, women and healthcare professionals, [13][14][15][16][17][18] and none in the general population or in extraordinary situations such as the COVID-19 pandemic.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In the current study, 56.5% of respondents endorsed scores of 25 or higher ( M = 21.1, SD = 7.2 for age-matched peers [ 33 ]), meaning over half of the students in the sample reported stress levels substantively higher than that of age matched peers in the U.S. population. Although high in comparison to the general population, such elevations on the Perceived Stress Scale are not uncommon and have been found in other samples, including doctoral level pharmacy students [ 39 , 40 ], Physician Assistant students [ 40 ]; doctoral level psychology students [ 41 ], and practicing health service professionals (i.e., dietician/nutrition professionals, nurses, physicians, social workers) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects on self-care seemed to be carried by the mindfulness aspect of acceptance techniques taught as part of the ACT course. These differential effects underscore evidence pointing to trainee self-care as a multidimensional construct (Ayala, Ellis, Grudev, & Cole, 2017). A dismantling design that more carefully parses mindfulness and acceptance effects on selfcare skills training could be useful in designing training that is intended to foster self-care competency.…”
Section: Competency Problemsmentioning
confidence: 96%